Joint Modules and Internationalisation in Higher Education Reflections on the Joint Module «Comparative Studies in Adult Education and Lifelong Learning» - Egetenmeyer, Regina; Guimaraes, Paula; Németh, Balázs (Studien zur Paedagogik, Andragogik und Gerontagogik / Studies in Pedagogy, Andragogy, and Gerontagogy, 2017)
This volume places the development of the Joint Module «Comparative Studies in Adult Education and Lifelong Learning» (COMPALL) in the context of international development in higher education and adult education. Based on this framework, the authors discuss the development of the joint module in terms of its institutional and didactical structure as well as participants' motivation and diversity. The book is divided into three parts: (1) Internationalisation in Higher Education, (2) Internationalisation of Higher Education: The Case of Adult Education, and (3) Internationalisation of Higher Education: The Example of COMPALL.